The effect of the channel reliability factor in the MAP algorithm on turbo code performance in bluetooth systems - KAYA, İsmail; KAHVECİ, Salim (Elektrik : Turkish journal of electrical engineering & computer sciences, 2010)
The effects of the channel reliability factor on the performance of turbo decoders that use a maximum a posteriori probability algorithm are investigated for wireless communication fading channels, such as Bluetooth systems. The channel reliability factor is related to the channel signal-to-noise ratio. For various values of the channel reliability factor, the obtained performance curves of the maximum a posteriori probability algorithm are given for the case of DMx Bluetooth data packets. When the channel reliability factor increases, the bit-error-rate performance of the DMx Bluetooth data packets also increases over fading channels.